Being a Principal for Extended Educational Services at School: Perspectives on What Matters—Structure, Culture, and Leadership - Schuler, Patricia; Elvstrand, Helene; Bostroem, Lena (International Journal of Education Policy and Leadership, 2026)
Extended education includes a variety of activities outside regular school hours for children of all ages, supervised by the school principal. Despite varying experiences, the principal’s role has hardly been investigated. As principals play a crucial role in driving school development and educational change, it is important to understand how they view their leadership performance in relation to extended education. This study surveyed principals in Sweden and Switzerland using a problem-based semistructured questionnaire. Deductive qualitative content analysis showed that principals in both countries faced leadership difficulties related to extended education, including translating policy papers and unclear extended education goals into guidelines for staff. Staff diversity and group sizes were also hindering factors, in a context where the principal’s services were seen as setting the tone for the school climate.